2022
DOI: 10.1002/ar.24902
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of acupuncture and Western medicine for poststroke thalamic pain

Abstract: Poststroke thalamic pain (PSTP) is one of the most common sequelae following stroke. Analgesics, antidepressants, anticonvulsants, and surgical treatment are conventional treatment methods of PSTP, but these methods have limited efficacy, cost more, and cause a likelihood of adverse reactions. Clinical studies have shown that acupuncture has a significant analgesic effect on PSTP without obvious side effects. But, there is a lack of high‐quality evidence concerning its effectiveness and safety to support its u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[23] At present, there are few meta-analyses on acupuncture for thalamic pain. [24,25] Therefore, this study evaluated the safety and efficacy of acupuncture versus medication in the treatment of thalamic pain based on scientific evidence.…”
Section: Introductionmentioning
confidence: 99%
“…[23] At present, there are few meta-analyses on acupuncture for thalamic pain. [24,25] Therefore, this study evaluated the safety and efficacy of acupuncture versus medication in the treatment of thalamic pain based on scientific evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to medical and surgical therapy, acupuncture has the advantages of minimal side effects and low cost in treating poststroke thalamic pain. To further clarify the safety and effectiveness of acupuncture, Yang and his group searched the database (PubMed, the Cochrane Library, EMBASE, the China National Knowledge Infrastructure, Wan Fang Database, and the Chinese Scientific Journal Database VIP) and systematically evaluated the randomized controlled trials (Yang et al, 2023). The results showed that the total effective rate of acupuncture in treating poststroke thalamic pain are reported to be greater than conventional therapies, with particular improvement of patients' visual analog score, beta‐endorphin content and reduction of adverse reactions (Yang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%